Accounting for effects of decreasing bond between concrete and rebars on seismic resistance of reinforced concrete structural elements - Benin, Andrey V. (Journal of Civil Engineering and Management, 2005)
This study reviews an alternative of reinforced concrete finite element model as a system, where physical conditions for system components are recorded independently and, in addition, conditions for interaction of system components on their contact are also introduced. In this case, we are able to take into account all specific features of reinforcement, to trace the history of loading and destruction for each rebar. Basic specific feature of reviewed problem ascertains the necessity to use non‐linear stress‐strain ratio in reinforced concrete with consideration of specific features of reinforced concrete activity after cracking. Naturally, functional dependence describing this ratio varies along with the progress of rebars corrosion. Exactly, corrosion of rebars is the key reason for time‐dependent quality degrading of reinforced concrete structures. This problem stands for more urgency with respect to structures in seismic sensitive zones since such corrosion of rebars leads to deviations of the structure rigidity characteristics and, in turn, it may lead to an reduction of bearing capability in certain elements or to an increase of displacements to intolerable high values. This study proposes a clarified procedure to solve plane‐stressed problem for reinforced concrete. The specific feature of this procedure assumes an application of new approximation for non‐linear concrete strain diagram, development of a detailed finite element model for reproduction of effect generated under concrete/rebar bond forces, as well as such considerable time‐dependent factors as concrete creep and rebar corrosion.Betono ir armatūros sukibimo įvertinimas skaičiuojant gelžbetoninių elementų atsparumą seisminėms apkrovomsSantrauka. Apžvelgtas alternatyvus gelžbetoninių baigtinių elementų modelis, kuriame atskirai įvertintos kiekvieno sistemos elemento fizikinės sąlygos ir papildomai atsižvelgta į sistemos elementų tarpusavio sąveiką. Tokiu atveju atsiranda galimybė įvertinti specifines armatūros savybes, stebėti apkrovimo istoriją ir kiekvieno strypo irimą. Sprendžiant aprašytą problemą reikia įvertinti netiesinį gelžbetonio įtempių‐deformacijų būvį, atsiradus plyšiams elemente. Be abejo, šiam būviui aprašyti taikoma funkcija priklauso nuo strypų korozijos lygio. Būtent strypų korozija yra pagrindinis veiksnys, lemiantis gelžbetoninių elementų degradaciją laikui bėgant. Ši problema ypač aktuali konstrukcijas eksploatuojant seisminėse zonose, kadangi strypų korozija mažina elemento standumą, o tai savo ruožtu sukelia jo laikomosios galios sumažėjimą arba įlinkių didėjimą iki neleistinų reikšmių. Pateikta aprašytos problemos sprendimo metodika, kuri taikoma gelžbetoninių elementų plokščiojo įtempių būvio atveju. Pagal šią metodiką taikoma nauja netiesinės betono įtempių‐deformacijų diagramos aproksimacija, sukurtas detalus baigtinių elementų modelis betono ir armatūros sukibimui įvertinti, atsižvelgta į laikui bėgant atsirandančius efektus, tokius kaip betono valkšnumas ir armatūros korozija.Raktiniai žodžiai: gelžbetonis, baigtiniu elementu modelis, netiesinės deformacijos, strypų korozija, seisminis smūgis.First Published Online: 14 Oct 2010